Factors associated with poor social support among Persons Living with HIV/AIDS at the Infectious Disease Institute HIV/AIDS clinic in Uganda, 2019: A cross-sectional study - Nakamanya Kitibwakye, Sharon; Kitutu, Freddy Eric; Nabakooza Kigongo, Angella; Olum, Ronald; Katana, Elizabeth; Laker, Eva (Research Square, 2019)
Social support is known to influence desired health outcomes resulting in decrease in morbidity and mortality. HIV patients with poor social support are at risk of worse health outcomes. Little is known about the determinants of social support in the HIV population in Uganda. This study examined the determinants of social support among HIV patients on Atazanavir-based regimen at the Infectious Disease Institute HIV/AIDS clinic in Uganda. Methods We carried out a secondary analysis of data nested in a cross-sectional study to determine the prevalence of clinical jaundice among patients on Atazanavir-based second-line therapy, which was conducted at a specialist HIV center, Infectious Disease Institute (IDI) in Kampala, Uganda from April to May 2019. IDI is a specialist HIV center in Kampala, Uganda with over 7000 patients in care. The primary study consecutively sampled patients on an Atazanavir- based regimen. Social support was assessed by using a 3-item Oslo social scale. Logistic regression was used to determine the association between social support and its correlates. Results Data from 236 participants with the mean age of 40 years ±11 was analyzed. The majority were females (66.5%) and 34% were married. Up to 16.5% (39/236) had other comorbidities and less than 1% (2/236) were depressed. There was a high level of disclosure of status to either a family member, friend, spouse, or children (94%; 221/236). The prevalence of internalized stigma (4%; 9/236) and depression (2/236; 1%) was low. Only disclosure of HIV status was associated with social support (OR= 4.9, 95% CI 1.1 – 21.3, p-value= 0.038). There was no significant association of age, sex, marital status, education status, religion, other chronic comorbidities, depression, drug fatigue, and stigma with social support. Conclusion We found that good/ moderate social support was associated with disclosure of HIV status. However, the relationship between social support and disclosure of HIV status warrants further exploration using qualitative research methods.
Keywords: Social support; Disclosure of HIV status; Persons Living with HIV/AIDS